Evaluation of the Conformity of Class 8 Indonesian Language Textbooks with National Education Standards - Haris, Abdul; Simamora, Enjelina Pitri; Hutasoit, Trides Mayora; Pardede, Nanda Claudia; Syuhada, Agung Dzaky; Hanum, Inayah (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This study aims to evaluate the suitability of grade 8 Indonesian textbooks with the National Education Standards. The research method used is content analysis using assessment rubrics prepared based on criteria in the National Education Standard. The results showed that the evaluated textbooks had a good level of conformity with the National Education Standards in terms of material and presentation, but still needed improvement in terms of language and learning evaluation. In conclusion, the textbook can be used with some adjustments to meet the National Education Standards.